Development of Soft Skills in Teaching English to Agriculture Students - Ruminar, Hafida (UIBU, 2024)
This study investigates the integration of soft skills within English learning experiences for English for Business Class participants, focusing on their relevance to future careers in agriculture. A narrative research design was employed in the study to delve into participants' English learning journeys and identify the most pertinent soft skills cultivated through learning activities. Semi-structured interviews are the primary data collection technique, allowing in-depth exploration of participants' experiences. Language appraisal and emotional geography analyses dissect the narratives and discern the most relevant soft skills for agricultural graduates. The analysis reveals many soft skills, including communication, problem-solving, decision-making, digital literacy, leadership, teamwork, critical and creative thinking, presentation skills, and reflection, all essential for navigating the complexities of agricultural work environments. These findings underscore the importance of integrating soft skills into English language learning curricula, particularly for students pursuing careers in agriculture. The study has implications for updating learning methodologies, refining teaching materials, and designing English learning activities tailored to the specific needs of agricultural professionals.